MANAGING CROSS-BORDER “DIGITAL SUCCESSION” IN THE DIGITAL ERA: PRELIMINARY REMARKS ON THE NEW CHALLENGES FOR THE CURRENT LEGAL FRAMEWORK (EU and comparative law issues and challenges series (ECLIC), 2023)
This paper aims to answer to a rather common question: what happen to our digital estate when we die? To do so, after analysing the composition of a digital estate, the paper will determine, firstly, the legal framework applicable to a cross-border succession to a digital estate. It will then investigate: (i) which assets are transferable upon death and to what extent; (ii) under what conditions heirs have access to the deceased’s accounts; and (iii) which interests on the digital content created by the deceased are protected and how. The analysis will be conducted through the lens of the current private international law framework in force in EU Member States, in order to formulate some preliminary remarks on its adequacy to manage this new succession phenomenon and the issues it raises.